Social Entrepreneurship as an Innovative Strategy for Social Development: Model Analysis and Its Challenges - Asykur, Muamar; Hanafi, Ali; Tamang, Andi (Association Of Indonesian Entrepreneurship Study Programs, 2024)
This research aims to analyze the concept and implementation of social entrepreneurship as an innovative approach in solving social problems in a sustainable manner. In the context of increasing social inequality, environmental crises, and limited state intervention, social entrepreneurship exists as an alternative that combines social orientation and business logic. This study uses a descriptive qualitative method with a literature study approach on a number of social entrepreneurship initiatives in Indonesia, such as Du'Anyam, Kopernik, and Waste4Change. The results show that social entrepreneurship has succeeded in creating real social impact by empowering marginalized communities, increasing access to environmentally friendly technologies, and managing resources sustainably. The success of this model is determined by three main factors, namely alignment with the social mission, innovation in products or services, and the sustainability of the business model. In conclusion, social entrepreneurship not only contributes to solving social problems, but also creates a more inclusive and resilient participatory development model. Therefore, this approach should be encouraged through public policy, multi-sectoral collaboration, and integration in the higher education curriculum